Interaction of temperature and light on seed germination in Tecoma stans L. Juss. ex Kunth (Bignoniaceae) - Socolowski,Fábio (2008)
The effects of the temperature and light on the control of seeds germination in Tecoma stans was studied in the present work. The influence of constant temperatures from 10 to 45ºC, with 5ºC intervals, under the white light and darkness were tested. The optimum temperature for the germination of the seeds was between 25 and 30ºC, for both the light and the dark treatments. The maximal germination was reached in the range of 15 to 35ºC under the light and of 20 to 40ºC in the darkness. The seeds showed highest synchronization of the germination near the optimal temperature. The germination in the field was tested under the two light conditions. The highest percent of germination occurred under the direct sunlight (86.1%) than under the canopy (69%). However, under the canopy, the seedling presented 1.5% of the recruitment, while under the direct sunlight, 96.9 %. Results showed that T. stans seeds germinated well in the open areas with the occurrence of high seedling recruitment indicating the invasion potential of the species in such light conditions.